Fibrosarcoma over the tarsal groove of a 14-month-old Quarter horse - Story, M. R.; Gaughan, E. M.; Andrews, G. A.; Balch, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
A 14-month-old male Quarter horse was presented for evaluation of a grade 3 out of 5 (grade 0=sound; grade 5=non-weight bearing) right rear lameness. A firm, 8 x 16 cm mass was palpable at the caudal medial aspect of the distal tibia and proximal tarsal region of the right hind limb. A percutaneous needle aspirate contained mesenchymal cells that were moderate to large in size with single, oblong nuclei. Differential diagnoses included fibrous hyperplasia, fibroma, or well-differentiated fibrosarcoma. Excisional biopsy for both definitive diagnosis and treatment was offered and selected by the owner. A fibrosarcoma was confirmed by histological examination of the mass. One and a half years after resection signs of lameness or evidence of regrowth of the mass were not evident.
Keywords: Horse; tumour; fibrosarcoma